How to kill the honey bee larva: genomic potential and virulence mechanisms of Paenibacillus larvae. - Marvin Djukic; Elzbieta Brzuszkiewicz; Anne Fünfhaus; Jörn Voss; Kathleen Gollnow; Lena Poppinga; Heiko Liesegang; Eva Garcia-Gonzalez; Elke Genersch; Rolf Daniel (PLoS ONE)
Paenibacillus larvae, a Gram positive bacterial pathogen, causes American Foulbrood (AFB), which is the most serious infectious disease of honey bees. In order to investigate the genomic potential of P. larvae, two strains belonging to two different genotypes were sequenced and used for comparative genome analysis. The complete genome sequence of P. larvae strain DSM 25430 (genotype ERIC II) consisted of 4,056,006 bp and harbored 3,928 predicted protein-encoding genes. The draft genome sequence of P. larvae strain DSM 25719 (genotype ERIC I) comprised 4,579,589 bp and contained 4,868 protein-encoding genes. Both strains harbored a 9.7 kb plasmid and encoded a large number of virulence-associated proteins such as toxins and collagenases. In addition, genes encoding large multimodular enzymes producing nonribosomally peptides or polyketides were identified. In the genome of strain DSM 25719 seven toxin associated loci were identified and analyzed. Five of them encoded putatively functional toxins. The genome of strain DSM 25430 harbored several toxin loci that showed similarity to corresponding loci in the genome of strain DSM 25719, but were non-functional due to point mutations or disruption by transposases. Although both strains cause AFB, significant differences between the genomes were observed including genome size, number and composition of transposases, insertion elements, predicted phage regions, and strain-specific island-like regions. Transposases, integrases and recombinases are important drivers for genome plasticity. A total of 390 and 273 mobile elements were found in strain DSM 25430 and strain DSM 25719, respectively. Comparative genomics of both strains revealed acquisition of virulence factors by horizontal gene transfer and provided insights into evolution and pathogenicity.